Pengaruh Motivasi Kerja dan Beban Kerja terhadap Kinerja Pegawai ASN pada Badan Pendapatan Daerah Kota Bogor - Andia Janash Mumthaza; Afriyanti Eva Belinda Lase; Irfan Achmad Musadat; Niken Widyastuti; Harianto Simarmata (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2024)
This study aims to find out the picture of work motivation, workload, and employee performance, as well as analyze the magnitude of the influence of work motivation and workload on employee performance, both partially and simultaneously. The research method used is descriptive and verifiable with a quantitative approach. The study population included all employees of the Bogor City Regional Revenue Agency, namely 83 ASN, who were used as respondents using non-probability sampling techniques through a saturated sampling approach. The results of the study show that the overview of work motivation, workload, and employee performance in general is included in the sufficient category. Based on the results of the determination test, it is known that work motivation has an effect of 53.5% on employee performance, while workload has an effect of 13.9% on employee performance. Simultaneously, work motivation and workload had an effect of 61.9% on employee performance. Thus, the results of the hypothesis test prove that work motivation and workload have a significant effect on employee performance. These findings confirm that improving employee performance can be achieved through organizational strategies that are able to optimize work motivation and manage workload proportionally, so as to create a productive and sustainable work environment.